Strategi Peningkatan Moral Siswa di Era Digital: Kajian Sosiologis tentang Integrasi Edukasi Karakter dan Media Pembelajaran Interaktif di SMA Negeri 12 Pontianak - Octy Astrid Nasution; Yohanes Bahari (Departement of Mathematics Education, 2024)
Enhancing student morale in the digital era has become an increasingly important concern in education. In this context, this study focuses on how the integration of character education and interactive learning media can improve student morale in the digital era. This research aims to find out how the integration of character education and interactive learning media can improve student morale in the digital era and test whether the